Perancangan dan Realisasi Antena MIMO Mikrostrip 4x4 Patch Circular pada Frekuensi 2,4 GHz Untuk Aplikasi WLAN 802.11n - Annisa Rizky (Politeknik Negeri Malang, 2018)
The development of wireless technology is very rapid in line with the needs of users for high-speed, efficient, reliable and quality communication systems. One of the technologies favored by telecommunication service users is Wireless Fidelity (WiFi) which is already supported byMIMO technology. Multiple Input Multiple Output (MIMO) is a system consisting of more than one terminal or antenna on the transmitter and receiver sides. With the use of more than one antenna, MIMO supports transmission media specifications that require a large capacity in the communication system. This research discusses the design and realization of the MIMO 4x4 microstrip circular patch antenna that can work on the 2.4 GHz frequency band for WiFi technology applications. The inset feed method is used to get the impedance value that matches between the patch and the line. To increase gain, a linear array method is used for each antenna. Testing the effect of the distance between antennas on the mutual coupling value. As well as testing the signal strength performance of the antenna if implemented as an antenna device at the access point. The results of the MIMO 4x4 test results Circular Microstrip Patch show the value of Return Loss = -13.3 dB; Mutual Coupling = -39.3 dB; VSWR = 1.482; Signal Strength = -25 dB.